2017
DOI: 10.21018/rjcpr.2017.1.231
|View full text |Cite
|
Sign up to set email alerts
|

Women Gossip and Men Brag: Perceived Gender Differences in the Use of Humor by Romanian Older Women

Abstract: The present study investigates perceived gender differences in the producion and social use of humor in the interpersonal communication of Romanian older women, aged 60 and above. The study is a qualitative investigation, based on semi-structured interviews. The aim was to understand the perceptions and motivations that women have when using humor in social interactions, and to explore the functions that humor serves in their day-to-day communication. A previous quantitative investigation found statistically s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Whereas earlier studies showed that sexist humor (i.e., humor that upholds gender role stereotypes) is preferred over non-sexist humor ( Cantor, 1976 ), other studies report that both men and women prefer humor that has the opposite gender as the butt ( Vaid and Hull, 1998 ; Parekh, 1999 ). Furthermore, men typically rate themselves higher than women in humor initiation whereas women tend to rate themselves higher in humor appreciation, but when humor is studied in actual conversational contexts a more nuanced picture emerges (see Kramarae, 1981 ; Kotthoff, 1996 , 2000 ; Schiau, 2017 ). Similarly, whereas some studies have found that humor produced by men is judged to be more humorous than that produced by women ( Brodzinsky and Rubien, 1976 ), other studies have not found this effect ( Hull et al, 2017 ), and still other work suggests a bias operating, whereby men are perceived to be the “funnier sex” regardless of how their humorous creations are actually judged ( Mickes et al, 2011 ; Hooper et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas earlier studies showed that sexist humor (i.e., humor that upholds gender role stereotypes) is preferred over non-sexist humor ( Cantor, 1976 ), other studies report that both men and women prefer humor that has the opposite gender as the butt ( Vaid and Hull, 1998 ; Parekh, 1999 ). Furthermore, men typically rate themselves higher than women in humor initiation whereas women tend to rate themselves higher in humor appreciation, but when humor is studied in actual conversational contexts a more nuanced picture emerges (see Kramarae, 1981 ; Kotthoff, 1996 , 2000 ; Schiau, 2017 ). Similarly, whereas some studies have found that humor produced by men is judged to be more humorous than that produced by women ( Brodzinsky and Rubien, 1976 ), other studies have not found this effect ( Hull et al, 2017 ), and still other work suggests a bias operating, whereby men are perceived to be the “funnier sex” regardless of how their humorous creations are actually judged ( Mickes et al, 2011 ; Hooper et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%